Research on Psychological Scales Based on the Multitheory Fusion - Liu, Guangdi; Li, Yu C.; Wang, Yue; Liu, Jing Xiang; Sang, Yong Sheng; Zhang, Wei; Zhang, Le (Current Bioinformatics, 2020)
Objective: This study proposed an innovative approach to simplify the multiple psychological scales for children and adolescents by integrating statistical methods and item reflection theory into a structural equation model. Methods: First, a psychological scale for adolescents to replace the existing scales optimized for adults with the Delphi method has been developed. Second, the number of items in the current group of scales has been reduced. Result and Conclusion: A psychological scale for adolescents has been built up that comprehensively reflects their psychological characteristics in terms of mental state, behavioral status, emotion & feeling, relationship, and environmental adaptation. This psychological scale has been simplified and improved its reliability and validity.
Keywords: model modification